IMPROVING SPARE PART INVENTORY SYSTEM MANAGEMENT BY USING 5S PRACTICES IN CONSUMER GOODS COMPANY - Sonny Aji; Aina Nindiani (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2022)
The spare part inventory is an important section that must be managed and controlled in the company, primarily because this section supports the provision of spare parts for the manufacturing process. An excellent spare part inventory management system matches the records in the SAP system in the warehouse and the actual physical evidence. The problem faced by the consumer goods company was the difference between recording in the SAP system and the physical evidence for non-consumable goods. By implementing improvements to the spare part management system for receiving and picking up goods in the warehouse, data discrepancies can be eliminated on non-consumable spare parts consisting of refurbished and new spare parts. The improvement was implementing the transit area and the 5S practices in the activities conducted in the spare part warehouse. The transit area is intended for comprehensive checking between warehouse personnel and other department involved with the goods stored or picked up. Refurbished and new items are more organized, making it easier to place and pick up items.